Eastern and Southern Africa policy roundtable on enhancing integration of agroecology into the post-Malabo Comprehensive Africa Agriculture Development Programme (CAADP) process - Recha, John W.M.; Barungi, Julian; Odeke, Moses; Magagula, Futhi; Gitau, Angela; Radeny, Maren A.O. (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Agricultural landscapes depend on these ecosystem services, and therefore, these environmental hazards threaten the viability and sustainability of agriculture and livestock production. Agricultural policy in many countries continues to reward unsustainable practices primarily through chemical input subsidies. The policy incentives have considered agriculture as any other industrial activity with standardized processes and ignored the dependence of agriculture on soil and ecosystems. This has led to depleted soil fertility, degraded soil, loss of the above ground biodiversity, and undermined the resilience and long-term viability of farming systems. The increasing dependence on natural resources exacerbates the pressure on sensitive ecosystems and ultimately affects both livelihoods and the economy. Therefore, transforming the human relationship with nature is key to a sustainable future. A significant contribution towards such re-balancing can be made through strengthening the adoption of agroecological practices.It is against this background that the CAADP-XP4 consortium partners comprising of the Association for Strengthening Agricultural Research in Eastern and Central Africa (ASARECA); African Forum for Agricultural Advisory Services (AFAAS), Center for Coordination of Agricultural Research for Development in Eastern and Southern Africa (CCARDESA), WECARD/CORAF and the Forum for Agricultural Research in Africa (FARA) are jointly organizing a regional policy roundtable on enhancing integration of agroecology into the post-Malabo CAADP Process. The overall objective of the side event was stakeholders to discuss and agree on a roadmap for integrating agroecology into implementation of the post-Malabo CAADP interventions at national level. The specific objectives were:  Share practical success stories and evidence on the economic, social and long-term benefits of agroecology and its role in agricultural transformation in Africa.  Discuss policy entry points and strategies for integrating agroecological practices in the post-Malabo CAADP interventions.  Identify policy opportunities and mechanisms for strengthening regional cooperation and policy coherence in scaling agroecology interventions at regional and national levels.  Identify gaps, challenges and lessons learned in policy and institutional support for integrating agroecology within the post-Malabo CAADP Strategy and Action Plan implementation.  Develop a roadmap with an M&E framework and concrete policy actions for mainstreaming agroecology in the post-Malabo CAADP Strategy and Action Plan implementation.